TINJAUAN HUKUM EKONOMI SYARI’AH TERHADAP PENETAPAN TARIF UANG TEBUSAN PADA PASAL 4 UNDANG UNDANG REPUBLIK INDONESIA NOMOR 11 TAHUN 2016 TENTANG PENGAMPUNAN PAJAK (TAX AMNESTY) - Wulan, Damar; Junaidi, Heri; Sunaryo, Sunaryo (Muamalah, 2018)
ABSTRACT Damar Wulan, the tittel Sharia Economic Law Review On Against Stipulation of Money Laundering at Article 4 of Law Number 11 of 2016 on Tax Amnesty. Two things were raised as a research focus. Firstly, How is the determination of ransom money on article 4 of the Law of the Republic of Indonesia Number 11 Year 2016 on Tax Amnesty. Secondly, How to review of the Law on Sharia Economy on the determination of the redemption fee in article 4 of the Republic of Indonesia Law No. 11 of 2016 on Tax Amnesty. Damar Wulan, the tittel Sharia Economic Law Review On Against Stipulation of Money Laundering at Article 4 of Law Number 11 of 2016 on Tax Amnesty. Two things were raised as a research focus. Firstly, How is the determination of ransom money on article 4 of the Law of the Republic of Indonesia Number 11 Year 2016 on Tax Amnesty. Secondly, How to review of the Law on Sharia Economy on the determination of the redemption fee in article 4 of the Republic of Indonesia Law No. 11 of 2016 on Tax Amnesty. This research is a library research, which collects data or scientific papers with data collection that is literature-based, or review carried out to solve a problem that is basically based on a critical and in-depth review of relevant library materials. Based on the data it is concluded that from the description presented there are various reviews, then the writer concludes that Tax Amnesty is a time-bound opportunity for certain taxpayers to pay a certain amount of taxes as a pardon for tax payable (including eliminating interest and penalties) relating to the previous tax period without fear of criminal prosecution. The program ended when tax authorities began tax investigations from previous periods. The determination of the ransom rate on Article 4 of the Tax Amnesty law based on the rules. Key Words: Uang tebusan, Tax Amnesty, Undang Undang Pajak